Sneaking tactics for mating of subordinate males - เลี้ยงพรพรรณ สุปาณี (Health Science, Science and Technology Reviews, 2018)
Females typically mate with dominant males than subordinate males. When subordinate males unable to attract females themselves, they sneak mating. There are specific sneaking tactics and strategies among invertebrate, fish, amphibian and bird. The fertilized success depends on sperm competition of sneaks and guards.